Enlarging parallel robot workspace through Type-2 singularity crossing. (June 2015) - Pagis, Georges; Bouton, Nicolas; Briot, Sebastien; Martinet, Philippe
Abstract: In order to increase the reachable workspace of parallel robots, a promising solution consists of the definition of optimal trajectories that ensure the non-degeneracy of the dynamic model in the Type 2 (or parallel) singularity. However, this assumes that the control law can perfectly track the desired trajectory, which is impossible due to modeling errors. This paper proposes a robust multi-model approach allowing parallel robots to cross Type 2 singularities. The main idea is to shift near singularities to a simplified dynamic model that can never degenerate. The two main contributions are the definition of an optimal trajectory crossing Type 2 singularities and the multi-model control law allowing to track this trajectory. The proposed control law is validated experimentally through a Five-bar planar mechanism.